Efficiency of application of means of sports preparation of combat sportsmen in physical training of students of technical high school - A.M. Litvinenko (Physical Education of Students)
The problem of efficiency of application of different volumes of trainings facilities of sporting single combats (on the example of kickboxing) is considered in physical education of students. The complexity of influence of facilities of east single combats is shown on sportsmen. In an experiment took part 50 students of first-year of teaching in age 17-18 years. Tests were used: undercutting on a cross-bar, broad jumps from a place, at shuttle run of 4х9 m. Positive intercommunication of increase of volume of the training loading is shown by effectiveness of pedagogical process. It is set that increase of number of employments by students in kickboxing to three one time per a week allows for certain to improve the indexes of physical preparedness on the chosen tests. The higher level of technical preparedness of students is statistically confirmed applying the greater amount of physical exercises, sent to forming of skills of kickboxing. Distribution of students is educed on the tactical types of conduct of competition fight: 36 % is a playing manner, 44 % is a rate manner, 8 % is a manner of slog, 12 % is an universal manner. Offered to recommendation on the correction of volume of loading for the increase of didactic potential of employments on physical education.